2021
DOI: 10.1186/s40659-021-00331-9
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MALAT1 aggravates oxygen‐glucose deprivation/reoxygenation-induced neuronal endoplasmic reticulum stress and apoptosis via the miR-195a-5p/HMGA1 axis

Abstract: Background This study aimed to investigate the potential role and molecular mechanism of lncRNA metastasis associated lung adenocarcinoma transcript 1 (MALAT1) in cerebral ischemia/reperfusion injury. Results Using an oxygen-glucose deprivation/reoxygenation (OGD/R) cell model, we determined that the expression of MALAT1 was significantly increased during OGD/R. MALAT1 knockdown reversed OGD/R-induced apoptosis and ER stress. Mechanistically, MALAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…LncRNA MALAT1 has been reported to be highly expressed in both in vivo and in vitro models of ischemia ( Guo et al, 2017 ; Zhang G. et al, 2020 ; Jia et al, 2021 ). In addition, It has also been claimed that downregulation of MALAT1 expression alleviates neuronal apoptosis.…”
Section: Regulatory Roles Of Lncrnas In Neuronsmentioning
confidence: 99%
See 2 more Smart Citations
“…LncRNA MALAT1 has been reported to be highly expressed in both in vivo and in vitro models of ischemia ( Guo et al, 2017 ; Zhang G. et al, 2020 ; Jia et al, 2021 ). In addition, It has also been claimed that downregulation of MALAT1 expression alleviates neuronal apoptosis.…”
Section: Regulatory Roles Of Lncrnas In Neuronsmentioning
confidence: 99%
“…Furthermore, miR-375 targets both MALAT1 and phosphodiesterase 4D (PDE4D) ( Zhang G. et al, 2020 ). It has also been reported that MALAT1 knockdown causes a reversal in OGD/R-induced apoptosis and endoplasmic reticulum stress through the targeting of miR-195a-5p and regulating the expression of high mobility group AT-hook1 (HMGA1) ( Jia et al, 2021 ).…”
Section: Regulatory Roles Of Lncrnas In Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a general theme, many lncRNAs act via sponging of specific miRNAs (e.g., [68,69]). For example, MALAT1 promotes oxygen-glucose deprivation/reoxygenation (OGD/R)-induced neuronal injury through ceRNA mechanisms [32,33]. Similarly, the beneficial effect of NORAD on cell survival was attributed to its miRNA sponging capacity [70].…”
Section: Discussionmentioning
confidence: 99%
“…Among these uncharacterized ncRNAs is MALAT1 (Metastasis-associated lung adenocarcinoma transcript 1; expression level ranked 99.94% of all ncRNA-expressed genes). The MALAT1 gene was shown to have a neuroprotective role in AD and Parkinson's disease (PD) [32,33]. MALAT1 also protects hippocampal neurons against autophagy, apoptosis [34] and ischemia [35].…”
Section: Lncrna Expression Levels In Sh-sy5y Cellsmentioning
confidence: 99%